Kepuasan kerja, komitmen organisasi dan niat berhenti kerja dalam kalangan pekerja sektor pembuatan di Selangor - Hasbullah @ Abdullah, Muslihah; Abd. Latif, Nur ‘aqilah (Malaysian Psychological Association, 2024)
This study aims to determine the relationships between the respondent's background (age, gender, monthly income and length of service), job satisfaction, organizational commitment and turnover intention among manufacturing sector workers. A total of 174 workers in two electronics factories in Bangi were randomly selected in this study. Data was collected using a self-administered questionnaire. Minnesota Satisfaction Questionnaire (Weiss, Dawis, England & Lofquist, 1967), Organizational Commitment Questionnaire (Allen & Meyer, 1990) and Turnover Intention Questionnaire (Wayne, Shore & Liden, 1997) were used to measure job satisfaction, organizational commitment and turnover intention. The results of the study found that most respondents have a moderate level of job satisfaction, organizational commitment and turnover intention. The study also shows that job satisfaction (r= -.298, p<0.01), affective commitment (r=-.510, p<0.01) and normative commitment (r = -.266, p<0.01) have a significant negative relationships with the turnover intention among respondents in the manufacturing sector. By implication, the results of this study provide an opportunity for organizations to re-evaluate employment policies including benefits for employees, in order to identify factors that have a negative impact on the level of job satisfaction and organizational commitment of employees. Organizations should conduct programs and training as well as diversify the incentives for employees who are able to increase job satisfaction and organizational commitment to increase productivity and stay with the organization.